Recent advances in photothermal nanomaterials for ophthalmic applications - Zhuang, Jiayuan; Jia, Linhui; Li, Chenghao; Yang, Rui; Wang, Jiapeng; Wang, Wen-an; Zhou, Heng; Luo, Xiangxia (Beilstein Journal of Nanotechnology, 2025)
The human eye, with its remarkable resolution of up to 576 million pixels, grants us the ability to perceive the world with astonishing accuracy. Despite this, over 2 billion people globally suffer from visual impairments or blindness, primarily because of the limitations of current ophthalmic treatment technologies. This underscores an urgent need for more advanced therapeutic approaches to effectively halt or even reverse the progression of eye diseases. The rapid advancement of nanotechnology offers promising pathways for the development of novel ophthalmic therapies. Notably, photothermal nanomaterials, particularly well-suited for the transparent tissues of the eye, have emerged as a potential game changer. These materials enable precise and controllable photothermal therapy by effectively manipulating the distribution of the thermal field. Moreover, they extend beyond the conventional boundaries of thermal therapy, achieving unparalleled therapeutic effects through their diverse composite structures and demonstrating enormous potential in promoting retinal drug delivery and photoacoustic imaging. This paper provides a comprehensive summary of the structure–activity relationship between the photothermal properties of these nanomaterials and their innovative therapeutic mechanisms. We review the latest research on photothermal nanomaterial-based treatments for various eye diseases. Additionally, we discuss the current challenges and future perspectives in this field, with a focus on enhancing global visual health.
Keywords: multifunctional composite; ophthalmology; photothermal nanomaterial; thermal field distribution; vapor nanobubble